Experimental evaluation of rectangular reinforced concrete column behaviour under biaxial cyclic loading - Hugo Rodrigues (2013)
The cyclic behaviour of reinforced concrete columns has been the subject of many experimental studies in recent years. However, most of these studies have focused on the unidirectional loading of columns with square cross-sections under constant axial loading conditions. In the present study, four types of full-scale quadrangular building columns were tested under different types of loading, including uniaxial and biaxial loading conditions. The first two specimens of each column type were independently cyclically tested in the strong and weak directions. Bidirectional tests using different loading paths were performed on the other column specimens. All columns were tested under constant axial loading conditions. In this paper, the experimental results are presented, and the global behaviour of tested columns is discussed, particularly focusing on the stiffness and strength degradation because of the increasing cyclic demand. Finally, the deformation-based performance limits proposed in Part 3 of Eurocode 8 were calculated and compared with the experimental results. Copyright (c) 2012 John Wiley & Sons, Ltd.